Consumers Quality And Safety Perception, Literature Review - Violeta GAGU (LEOCA); Gheorghe Adrian ZUGRAVU; Mirela CALU (Communications of International Proceedings, 2021)
The consumer perception of food-and-drink products is an important source of basic pleasure, using our human senses and it is very important to consider how the senses influence our perception. Certification is designedby food business operators in order to give confidence to the public in this management system in place and is a trade condition or a proactive action to ensure that all possible hazards are covered. Labeling is a means of communication used by the food producers in order to provide information to consumers about the quality and safety certification, which may determine whether or not the consumer purchases a food product.
Keywords: Management System; Quality And Safety Certification.